A diffusion layer and its preparation method and membrane electrode
By using porous carbon nanosheets and dopants in the diffusion layer of the fuel cell membrane electrode to form a sheet-like carbon layer structure, the problem of existing diffusion layer materials prone to collapse under high potential and water gas erosion is solved, and the membrane is significantly improved Durability of electrodes.
Patent Information
- Application Number
- CN202211654923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The diffusion layer materials of existing fuel cell membrane electrodes such as XC-72 or multi-walled carbon nanotubes are prone to structural collapse under water and gas erosion and high potential, resulting in poor durability.
The microporous layer material using porous carbon nanosheets as the diffusion layer is laminated, and the base layer and the microporous layer are arranged. The ratio of mesopora to microporosity is (45-55): (45-55), and lignin is passed. Dopants such as sodium sulfonate, urea and thiourea form a flake-like carbon layer structure to avoid structural collapse.
It significantly improves the durable polarization of the membrane electrode, can maintain the structural stability under high potential and water-gas erosion conditions, and extends the service life of the membrane electrode.
Smart Images

Figure CN115799554B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a diffusion layer and a preparation method thereof, and a membrane electrode. Background Art
[0002] Hydrogen fuel cell stacks have attracted attention due to their environmental friendliness and high power. The core part of hydrogen fuel cell stacks is the membrane electrode, which is composed of anode and cathode diffusion layers, cathode and cathode catalyst layers, proton exchange membranes, and cathode and cathode frames. Among them, the diffusion layer is composed of a base layer and a microporous layer. The diffusion layer supports the entire membrane electrode, and the microporous layer is the transmission channel for gas, water, electrons, and protons. The commonly used materials for the microporous layer are usually carbon materials XC-72 or multi-walled carbon nanotubes, but XC-72 or multi-walled carbon nanotubes are prone to structural collapse under the erosion of water vapor and are easily corroded at high potentials, which makes the membrane electrode have poor polarization durability. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a diffusion layer and a preparation method thereof and a membrane electrode. When the diffusion layer provided by the present invention is used as an anode and cathode diffusion layer in a membrane electrode, the durable polarization of the membrane electrode is improved.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a diffusion layer, comprising a base layer and a microporous layer which are stacked;
[0006] The material of the microporous layer is a porous carbon nanosheet; the porous carbon nanosheet includes mesopores and micropores; the ratio of the mesoporosity to the microporosity of the porous carbon nanosheet is (45-55): (45-55).
[0007] Preferably, the pore size of the mesopores is 2-5 nm, and the pore size of the micropores is 0.8-2 nm.
[0008] Preferably, the diffusion layer comprises an anode diffusion layer or a cathode diffusion layer;
[0009] In the anode diffusion layer, the loading amount of the porous carbon nanosheet relative to the base layer is 0.2-0.6 mg / cm 2 ;
[0010] When the cathode diffusion layer is used, the loading amount of the porous carbon nanosheet relative to the base layer is 0.6-1 mg / cm 2 .
[0011] The present invention also provides a method for preparing the diffusion layer described in the above technical solution, comprising the following steps:
[0012] dissolving and dispersing the activator, sodium lignin sulfonate and the doping agent to obtain a microporous layer slurry;
[0013] Applying the microporous layer slurry on the base layer and baking it to obtain the diffusion layer;
[0014] The doping agent includes urea and / or thiourea;
[0015] The activator includes an ammonium salt.
[0016] Preferably, the ammonium salt comprises one or more of ammonium chloride, ammonium sulfate and ammonium nitrate.
[0017] Preferably, the mass ratio of the ammonium salt to sodium lignin sulfonate is (0.5-0.8):1.
[0018] Preferably, the mass of the dopant is 10% to 20% of the mass of the sodium lignin sulfonate.
[0019] Preferably, the dispersion temperature is 320-350° C. and the dispersion time is 30-40 min.
[0020] Preferably, the calcination temperature is 500-800° C., and the calcination time is 0.5-1 h; the calcination is performed under a protective atmosphere, and the protective atmosphere includes an inert gas or nitrogen.
[0021] The present invention also provides a membrane electrode, comprising an anode diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode diffusion layer which are stacked in sequence;
[0022] The anode diffusion layer and the cathode diffusion layer are the diffusion layers described in the above technical solution.
[0023] The present invention provides a diffusion layer, including a stacked base layer and a microporous layer; the material of the microporous layer is a porous carbon nanosheet; the porous carbon nanosheet includes mesopores and micropores; the ratio of the mesoporosity to the microporosity of the porous carbon nanosheet is (45-55): (45-55). The diffusion layer of the present invention uses porous carbon nanosheets as the microporous layer material. Since the mesoporosity and microporosity of the porous carbon nanosheets are equivalent and evenly distributed, a three-phase reaction interface can be effectively formed, thereby shortening the ion diffusion path, improving the contact between the electrolyte and the electrode, and ultimately improving the durable polarization of the membrane electrode. The data of the embodiment show that the membrane electrode made of the diffusion layer of the present invention has a current density of 1.69A / cm at 0.65V after a 100h durability test. 2 .
[0024] The present invention also provides a method for preparing the diffusion layer described in the above technical solution, comprising the following steps: dissolving an activator, sodium lignin sulfonate and a dopant, dispersing to obtain a microporous layer slurry; coating the microporous layer slurry on a substrate, and baking to obtain the diffusion layer; the dopant includes urea and / or thiourea; the activator includes an ammonium salt. Under the action of the dopant (urea and / or thiourea), the sodium lignin sulfonate of the present invention forms a sheet-like carbon layer structure, which can avoid the high potential, water scouring, and the collapse of the carbon structure; at the same time, the doping of urea and thiourea avoids the reaction of ammonium salt with sodium lignin sulfonate to produce crystals and then block the pores. In addition, under the action of ammonium salt and dopant (urea and / or thiourea), sodium lignin sulfonate can release gases such as ammonia and sulfur dioxide under baking conditions, thereby generating porous carbon nanosheets with equivalent mesoporosity and microporosity.
[0025] The present invention also provides a membrane electrode, comprising an anode diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode diffusion layer stacked in sequence; the anode diffusion layer and the cathode diffusion layer are the diffusion layers described in the above technical solution. Since the diffusion layer of the present invention uses porous carbon nanosheets as the microporous layer material, the durable polarization of the membrane electrode is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope photograph of the porous carbon nanosheet in the diffusion layer obtained in Example 1 before the durability test and polarization test;
[0027] Figure 2 This is a transmission electron microscope photo of the porous carbon nanosheet obtained in Example 1 after durability testing;
[0028] Figure 3 Polarization curves of the membrane electrodes obtained in Example 1 and Comparative Example 1 after 100 hours of durability test;
[0029] Figure 4 The polarization curves of the membrane electrodes obtained in Example 2 and Comparative Example 2 after 100 hours of durability test. DETAILED DESCRIPTION
[0030] The present invention provides a diffusion layer, comprising a base layer and a microporous layer which are stacked;
[0031] The material of the microporous layer is a porous carbon nanosheet; the porous carbon nanosheet includes mesopores and micropores; the ratio of the mesoporosity to the microporosity of the porous carbon nanosheet is (45-55): (45-55).
[0032] The diffusion layer provided by the present invention comprises a base layer. In the present invention, the base layer is preferably carbon paper, and the model of the carbon paper is preferably Avcarb EP45 or Avcarb EP55. In the present invention, the thickness of the carbon paper is preferably 180-250 μm.
[0033] The diffusion layer provided by the present invention includes a microporous layer stacked on the base layer. In the present invention, the material of the microporous layer is a porous carbon nanosheet; the porous carbon nanosheet includes mesopores and micropores; the ratio of the mesoporosity to the microporosity of the porous carbon nanosheet is (45-55): (45-55), preferably (46-48): (52-54). In the present invention, the pore size of the mesopore is preferably 2-5 nm, and the pore size of the micropore is preferably 0.8-2 nm.
[0034] In the present invention, the diffusion layer preferably includes an anode diffusion layer or a cathode diffusion layer.
[0035] In the present invention, the loading amount of the porous carbon nanosheets relative to the base layer in the anode diffusion layer is preferably 0.2 to 0.6 mg / cm 2 , more preferably 0.3 to 0.5 mg / cm 2 , more preferably 0.4 mg / cm 2 .
[0036] In the present invention, the cathode diffusion layer has a loading amount of the porous carbon nanosheet relative to the base layer of preferably 0.6 to 1 mg / cm 2 , more preferably 0.7 to 0.9 mg / cm 2 , more preferably 0.8 mg / cm 2 .
[0037] The present invention also provides a method for preparing the diffusion layer described in the above technical solution, comprising the following steps:
[0038] dissolving and dispersing the activator, sodium lignin sulfonate and the doping agent to obtain a microporous layer slurry;
[0039] Applying the microporous layer slurry on the base layer and baking it to obtain the diffusion layer;
[0040] The doping agent includes urea and / or thiourea;
[0041] The activator includes an ammonium salt.
[0042] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0043] The invention dissolves and disperses an activator, sodium lignin sulfonate and a doping agent to obtain microporous layer slurry.
[0044] In the present invention, the activator comprises an ammonium salt. In the present invention, the ammonium salt preferably comprises one or more of ammonium chloride, ammonium sulfate and ammonium nitrate, and more preferably ammonium chloride or ammonium nitrate.
[0045] In the present invention, the doping agent includes urea and / or thiourea.
[0046] In the present invention, the mass ratio of the ammonium salt to the sodium lignin sulfonate is preferably (0.5-0.8):1, and more preferably (0.6-0.7):1.
[0047] In the present invention, the mass of the dopant is preferably 10% to 20% of the mass of the sodium lignin sulfonate, more preferably 12% to 18%, and even more preferably 14% to 16%.
[0048] In the present invention, the dissolved reagent preferably includes water. In the present invention, the usage ratio of the ammonium salt to the dissolved reagent is preferably 20-30 g: 50-100 mL.
[0049] In the present invention, dissolving the activator, sodium lignin sulfonate and dopant preferably comprises: first mixing the activator and dissolved reagent to obtain an activator solution; and second mixing the activator solution, sodium lignin sulfonate and dopant. In the present invention, the first mixing time is preferably 10 to 20 minutes; and the first mixing method is preferably magnetic stirring.
[0050] In the present invention, the dispersion temperature is preferably 320 to 350° C., more preferably 330 to 340° C., and the dispersion time is preferably 30 to 40 min.
[0051] In the present invention, the dispersion method is preferably one or more of magnetic stirring, ball milling stirring and ultrasonic dispersion, and magnetic stirring is more preferably used.
[0052] The preparation method of the present invention does not use other organic solvents, so does not involve subsequent solvent treatment, which is beneficial to environmental protection.
[0053] After obtaining the microporous layer slurry, the present invention applies the microporous layer slurry on the base layer and bakes it to obtain the diffusion layer.
[0054] In the present invention, the base layer is preferably carbon paper, and the model of the carbon paper is preferably AvcarbEP45 or AvcarbEP55. In the present invention, the thickness of the carbon paper is preferably 180-250 μm. In the present invention, the base layer is preferably cleaned and dried before use; the cleaning method is preferably soaking; the soaking agent preferably includes anhydrous ethanol; the soaking time is preferably 24 hours.
[0055] In the present invention, the coating method is preferably scraping; the scraping parameters include: the scraper speed is preferably 1-2 mm / s, and the scraper thickness is preferably 1-2 mm.
[0056] In the present invention, the calcination temperature is preferably 500-800°C, more preferably 600-700°C; the time is preferably 0.5-1h. In the present invention, the calcination is preferably carried out under a protective atmosphere, and the protective atmosphere preferably includes an inert gas or nitrogen. In the present invention, the calcination is preferably carried out in a tubular furnace.
[0057] The present invention also provides a membrane electrode, comprising an anode diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode diffusion layer which are stacked in sequence;
[0058] The anode diffusion layer and the cathode diffusion layer are the diffusion layers described in the above technical solution.
[0059] In the present invention, the anode catalyst layer, proton exchange membrane and cathode catalyst layer stacked in sequence are commercially available CCM. In the present invention, the catalyst loading in the anode catalyst layer and the cathode catalyst layer in the CCM is preferably 0.35 mg / cm 2 In the present invention, the CCM is preferably Hongji Chuangneng XER350 or SER350.
[0060] In the present invention, the method for preparing the membrane electrode preferably comprises the following steps:
[0061] The anode diffusion layer, CCM and cathode diffusion layer are hot pressed to obtain the membrane electrode.
[0062] In the present invention, the temperature of the hot pressing is preferably 90-120° C., more preferably 100-110° C.; the pressure is preferably 90-120 MPa, more preferably 100-110 MPa; and the time is preferably 90-120 s, more preferably 100-110 s.
[0063] The diffusion layer and the preparation method thereof and the membrane electrode provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0064] Example 1
[0065] Weigh 20g of ammonium chloride white powder, dissolve it in 80mL of deionized water, and stir it magnetically for 10min to form an ammonium chloride solution. Weigh 40g of sodium lignin sulfonate, add it to the ammonium chloride solution, and then weigh 4g of urea powder and add it to the ammonium chloride solution. Heat it to 340℃ and stir it magnetically for 30min until the solution is in a molten state to obtain a microporous layer slurry.
[0066] Cut AVcarbEP45 as the base layer carbon paper of the cathode and anode, soak the carbon paper in anhydrous ethanol for 24 hours to remove impurities, and then take it out and dry it for use. Use a scraper to evenly apply the microporous layer slurry on the cathode and anode base layer carbon paper. The scraper speed is 1mm / s and the scraper thickness is 2mm. The cathode and anode base layer carbon paper coated with the microporous layer slurry are placed in a tubular furnace. Under argon protection, the temperature is raised to 700℃ and reacted for 1h. After taking it out, the cathode diffusion layer and the anode diffusion layer are obtained. The loading amount of porous carbon nanosheets in the cathode diffusion layer is 0.8mg / cm 2 The loading amount of porous carbon nanosheets in the anode diffusion layer is 0.4 mg / cm 2 .
[0067] The anode diffusion layer, XER350CCM, and cathode diffusion layer were arranged in sequence, placed in a hot press, and hot pressed for 90 seconds at a temperature of 120° C. and a pressure of 100 MPa to obtain a membrane electrode.
[0068] Example 2
[0069] Weigh 30g of ammonium nitrate white powder, dissolve it in 100mL of deionized water, and stir it magnetically for 20min to form an ammonium nitrate solution. Weigh 60g of sodium lignin sulfonate, add it to the ammonium nitrate solution, and then weigh 7g of thiourea powder and add it to the ammonium nitrate solution. Heat it to 350℃ and stir it magnetically for 30min until the solution is in a molten state to obtain a microporous layer slurry.
[0070] Cut AVcarbEP45 as the base layer carbon paper of the cathode and anode respectively, soak the carbon paper in anhydrous ethanol for 24 hours to remove impurities, and then take it out and dry it for use. Use a scraper to evenly apply the microporous layer slurry on the cathode and anode base layer carbon paper. The scraper speed is 2mm / s and the scraper thickness is 1mm. The cathode and anode base layer carbon paper coated with the microporous layer slurry are placed in a tubular furnace. Under nitrogen protection, the temperature is raised to 800℃, reacted for 1h, and the cathode diffusion layer and the anode diffusion layer are obtained after taking them out; among them, the loading amount of porous carbon nanosheets in the cathode diffusion layer is 0.6mg / cm 2 The loading amount of porous carbon nanosheets in the anode diffusion layer is 0.4 mg / cm 2 .
[0071] The anode diffusion layer, SER350CCM, and cathode diffusion layer were arranged in sequence, placed in a hot press, and hot pressed for 100 seconds at a temperature of 120° C. and a pressure of 120 MPa to obtain a membrane electrode.
[0072] Comparative Example 1
[0073] 40 g of XC-72 carbon powder was weighed as the microporous layer carbon material, added into 80 mL of isopropanol solvent, and magnetically stirred for 30 min to prepare the microporous layer slurry.
[0074] Cut AVcarbEP45 as the base layer carbon paper of the cathode and anode, soak the carbon paper in anhydrous ethanol for 24 hours to remove impurities, and then take it out and dry it for use. Use a scraper to evenly apply the microporous layer slurry on the cathode and anode base layer carbon paper. The scraper speed is 1mm / s and the scraper thickness is 2mm. The cathode and anode base layer carbon paper coated with the microporous layer slurry are placed in a tubular furnace. Under the protection of argon, the temperature is raised to 700℃ and reacted for 1h. After taking it out, the cathode diffusion layer and the anode diffusion layer are obtained. The loading amount of XC-72 carbon powder in the cathode diffusion layer is 0.8mg / cm 2 The loading amount of XC-72 carbon powder in the anode diffusion layer is 0.4 mg / cm 2 .
[0075] The anode diffusion layer, XER350CCM, and cathode diffusion layer were arranged in sequence, placed in a hot press, and hot pressed for 90 seconds at a temperature of 120°C and a pressure of 100 MPa to obtain a membrane electrode.
[0076] Comparative Example 2
[0077] 70 g of multi-walled carbon nanotubes (MWCNT) were weighed as microporous layer carbon materials, added into 100 mL of ethylene glycol, and magnetically stirred for 20 min to prepare microporous layer slurry.
[0078] Cut AVcarbEP45 as the base layer carbon paper for the cathode and anode, soak the carbon paper in anhydrous ethanol for 24 hours to remove impurities, and then take it out and dry it for use. Use a scraper to evenly apply the microporous layer slurry on the cathode and anode base layer carbon paper. The scraper speed is 2mm / s and the scraper thickness is 1mm. The cathode and anode base layer carbon paper coated with the microporous layer slurry are placed in a tubular furnace. Under nitrogen protection, the temperature is raised to 800℃ and reacted for 1h. After taking it out, the cathode diffusion layer and the anode diffusion layer are obtained. The loading amount of multi-walled carbon nanotubes in the cathode diffusion layer is 0.6mg / cm 2 The loading amount of multi-walled carbon nanotubes in the anode diffusion layer is 0.4 mg / cm 2 .
[0079] The anode diffusion layer, SER350CCM, and cathode diffusion layer were arranged in sequence, placed in a hot press, and hot pressed for 100 seconds at a temperature of 120° C. and a pressure of 120 MPa to obtain a membrane electrode.
[0080] Performance Testing
[0081] The mesoporosity and microporosity of the porous nanosheets in the diffusion layer obtained in Example 1 and Example 2 were tested by the BET method. The results showed that the mesopore (2-5 nm) rate of the porous nanosheets in the diffusion layer obtained in Example 1 was 48% and the micropore (0.8-2 nm) rate was 52%. The mesopore (2-5 nm) rate of the porous nanosheets in the diffusion layer obtained in Example 2 was 46% and the micropore (0.8-2 nm) rate was 54%.
[0082] Durability test: After a short activation, the battery was operated alternately at 60A-480A for 100h, with each current running for 10min, the current ramp rate was 15A / s, the anode stoichiometric ratio was 2.2, and the cathode stoichiometric ratio was 3.5. Anode humidity was 40%RH, cathode humidity was 60%RH, hydrogen back pressure was 120kPa, air back pressure was 100kPa, anode temperature was 75℃, cathode temperature was 75℃, and stack temperature was 78℃.
[0083] Polarization test conditions: After the endurance test, the scanning current density was 30A to 570A, and each current was operated for 30s, the current ramp rate was 15A / s, the anode stoichiometric ratio was 2.2, and the cathode stoichiometric ratio was 3.5. Anode humidity was 40% RH, cathode humidity was 60% RH, hydrogen back pressure was 120kPa, air back pressure was 100kPa, anode temperature was 75°C, cathode temperature was 75°C, and stack temperature was 78°C.
[0084] Figure 1 This is a transmission electron microscope photo of the porous carbon nanosheet in the diffusion layer obtained in Example 1 before the durability test and polarization test. Figure 2 This is a transmission electron microscope photo of the porous carbon nanosheet obtained in Example 1 after durability testing. Figure 1 and 2 It can be seen that the structure of the original microporous layer is a lamellar structure, in which the average thickness of the sheet is 7.5nm and the sheet structure is compact; after the durability test, the structure did not collapse under long-term high-potential operation.
[0085] Figure 3 The polarization curves of the membrane electrodes obtained in Example 1 and Comparative Example 1 after 100h durability test; Figure 3 It can be seen that the current density of the membrane electrode of Example 1 at 0.65V is 1.64A / cm 2 The current density of the membrane electrode of comparative example 1 at 0.65V is 1.54A / cm 2 .
[0086] Figure 4 The polarization curves of the membrane electrodes obtained in Example 2 and Comparative Example 2 after 100h durability test; Figure 4 It can be seen that the current density of the membrane electrode of Example 2 is 1.69A / cm at 0.65V.2 The current density of the membrane electrode of comparative example 2 at 0.65V is 1.59A / cm 2 This shows that under long-term operation at high potential, the drainage effect of the diffusion layer provided by the present invention is still very good, and the membrane electrode can still maintain excellent performance, proving that the present invention has unique excellence.
[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A diffusion layer, characterized in that: It includes a base layer and a microporous layer which are stacked; The material of the microporous layer is a porous carbon nanosheet; the porous carbon nanosheet includes mesopores and micropores; the ratio of the mesoporosity to the microporosity of the porous carbon nanosheet is (45-55): (45-55); The method for preparing the diffusion layer comprises the following steps: dissolving and dispersing the activator, sodium lignin sulfonate and the doping agent to obtain a microporous layer slurry; Applying the microporous layer slurry on the base layer and baking it to obtain the diffusion layer; The doping agent includes urea and / or thiourea; The activator includes an ammonium salt; The dispersion temperature is 320-350° C. and the dispersion time is 30-40 min.
2. The diffusion layer according to claim 1, characterized in that The pore size of the mesopore is 2-5 nm, and the pore size of the micropore is 0.8-2 nm.
3. The diffusion layer according to claim 1, characterized in that The diffusion layer includes an anode diffusion layer or a cathode diffusion layer; In the anode diffusion layer, the loading amount of the porous carbon nanosheet relative to the base layer is 0.2-0.6 mg / cm 2 ; When the cathode diffusion layer is used, the loading amount of the porous carbon nanosheet relative to the base layer is 0.6-1 mg / cm 2 .
4. The method for preparing a diffusion layer according to any one of claims 1 to 3, characterized in that: The following steps are involved: dissolving and dispersing the activator, sodium lignin sulfonate and the doping agent to obtain a microporous layer slurry; Applying the microporous layer slurry on the base layer and baking it to obtain the diffusion layer; The doping agent includes urea and / or thiourea; The activator includes an ammonium salt; The dispersion temperature is 320-350° C. and the dispersion time is 30-40 min.
5. The preparation method according to claim 4, characterized in that: The ammonium salt includes one or more of ammonium chloride, ammonium sulfate and ammonium nitrate.
6. The preparation method according to claim 4 or 5, characterized in that: The mass ratio of the ammonium salt to sodium lignin sulfonate is (0.5-0.8):
1.
7. The preparation method according to claim 4, characterized in that: The mass of the dopant is 10% to 20% of the mass of the sodium lignin sulfonate.
8. The preparation method according to claim 4, characterized in that: The calcination temperature is 500-800° C., and the calcination time is 0.5-1 h. The calcination is carried out under a protective atmosphere, and the protective atmosphere includes an inert gas or nitrogen.
9. A membrane electrode, characterized in that: It includes an anode diffusion layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer and a cathode diffusion layer which are stacked in sequence; The anode diffusion layer and the cathode diffusion layer are the diffusion layers according to any one of claims 1 to 3.
Citation Information
Patent Citations
Lignin-based flower-shaped carbon nano-material and preparation method and application thereof
CN106564876A
Polyatom-doped lignin carbon-based electrode material and preparation method thereof
CN115101353A